The Burnout Challenge : Managing People's Relationships with Their Jobs - Maslach, Christina (Harvard University Press, 2022)
Two pioneering researchers identify key causes of workplace burnout and reveal what managers can do to promote increased productivity and health.Burnout is among the most significant on-the-job hazards facing workers today. It is also among the most misunderstood. In particular, we tend to characterize burnout as a personal issue-a problem employees should fix themselves by getting therapy, practicing relaxation techniques, or changing jobs. Christina Maslach and Michael P. Leiter show why this is not the case. Burnout also needs to be managed by the workplace.Citing a wealth of research data and drawing on illustrative anecdotes, The Burnout Challenge shows how organizations can change to promote sustainable productivity. Maslach and Leiter provide useful tools for identifying the signs of employee burnout, most often exhaustion, cynicism, and ineffectiveness. They also advise managers on assembling and interpreting worker self-evaluation surveys, which can reveal workplace problems and potential solutions. And when it comes to implementing change, Maslach and Leiter offer practical, evidence-driven guidance. The key, they argue, is to begin with less-taxing changes that employees nonetheless find meaningful, seeding the ground for more thorough reforms in the future.Experts estimate that more than $500 billion and 550 million workhours are lost annually to on-the-job stress, much of it caused by dysfunctional work environments. As priorities and policies shift across workplaces, The Burnout Challenge provides pragmatic, creative, and cost-effective solutions to improve employee efficiency, health, and happiness.